Peran Diplomasi Budaya Korea Selatan dalam Membangun Konektivitas Global melalui Soft Power - Cahyani, Agista Nur; Rifai, Maulana; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
Soft Power is influence that is not military or economic in nature but is based on the appeal of a country's culture, values and positive image. South Korea has successfully utilized soft power through the Korean Wave to increase its visibility and influence in the international arena. This study aims to determine the role of Korean cultural diplomacy in building global connectivity through the concept of soft power. This research uses a qualitative descriptive research method. The results show that South Korea's cultural diplomacy, particularly through the Korean Wave, has successfully brought significant positive impacts. This research emphasizes the contribution of the Korean Wave in strengthening South Korea's good image at the global level, building socio-cultural and economic relations in East Asia, and creating economic growth through increasing the popularity of Korean products and lifestyles. Full government support, including through the establishment of public institutions, has provided a strong foundation for the success of South Korea's cultural diplomacy. Overall, this research shows that South Korea's cultural diplomacy is an effective instrument in building positive connectivity, the economy, and shaping global views of the country.